The strategic and operational characteristics of a distributed phased archive for a multivendor incremental implementation of picture archiving and communications systems...Proceedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston, TX, May 6-9, 1999 - Smith EM; Wandtke J; Robinson A (Journal of Digital Imaging)
The long-term (10 years) multimodality distributed phased archive for the Medical Information, Communication and Archive System (MICAS) is being implemented in three phases. The selection process took approximately 10 months. Based on the mandatory archive attributes and desirable features, Cemax-Icon (Fremont, CA) was selected as the vendor. The archive provides for an open-solution allowing incorporation of leading edge, 'best of breed' hardware and software and provides maximum flexibility and automation of workflow both within and outside of radiology. The solution selected is media-independent, provides expandable storage capacity, and will provide redundancy and fault tolerance in phase II at minimum cost. Other attributes of the archive include scalable archive strategy, virtual image database with global query, and an object-oriented database. The archive is seamlessly integrated with the radiology information system (RIS) and provides automated fetching and routing, automated study reconciliation using modality worklist manager, clinical reports available at any Digital Imaging and Communications in Medicine (DICOM) workstation, and studies available for interpretation whether validated or not. Within 24 hours after a new study is acquired, four copies will reside within different components of the archive including a copy that can be stored off-site. Phase II of the archive will be installed during 1999 and will include a second Cemax-Icon archive and database using archive manager (AM) Version 4.0 in a second computer room. Copyright (c) 1999 by W.B. Saunders Company